Lymphocytes Negatively Regulate NK Cell Activity via Qa-1b following Viral Infection - Haifeng C. Xu; Jun Huang; Aleksandra A. Pandyra; Elisabeth Lang; Yuan Zhuang; Christine Thöns; Jörg Timm; Dieter Häussinger; Marco Colonna; Harvey Cantor; Karl S. Lang; Philipp A. Lang (Cell Reports, 2017)
NK cells can reduce anti-viral T cell immunity during chronic viral infections, including infection with the lymphocytic choriomeningitis virus (LCMV). However, regulating factors that maintain the equilibrium between productive T cell and NK cell immunity are poorly understood. Here, we show that a large viral load resulted in inhibition of NK cell activation, which correlated with increased expression of Qa-1b, a ligand for inhibitory NK cell receptors. Qa-1b was predominantly upregulated on B cells following LCMV infection, and this upregulation was dependent on type I interferons. Absence of Qa-1b resulted in increased NK cell-mediated regulation of anti-viral T cells following viral infection. Consequently, anti-viral T cell immunity was reduced in Qa-1b- and NKG2A-deficient mice, resulting in increased viral replication and immunopathology. NK cell depletion restored anti-viral immunity and virus control in the absence of Qa-1b. Taken together, our findings indicate that lymphocytes limit NK cell activity during viral infection in order to promote anti-viral T cell immunity.